The Energy and Exergy of Light with Application to Societal Exergy Analysis - Matthew Kuperus Heun; Zeke Marshall; Emmanuel Aramendia; Paul E. Brockway (Energies, 2020)
Lighting provides an indispensable energy service, illumination. The field of societal exergy analysis considers light (and many other energy products) to be enablers of economic growth, and lighting contributes a non-negligible proportion of total useful exergy supplied to modern economies. In societal exergy analysis, the exergetic efficiency of electric lamps is central to determining the exergy contribution of lighting to an economy. Conventionally, societal exergy practitioners estimate the exergetic efficiency of lamps by an energy efficiency, causing confusion and, sometimes, overestimation of exergetic efficiency by a factor as large as 3. In response, we use recent results from the fields of radiation thermodynamics and photometry to develop an exact method for calculating the exergy of light and the exergetic efficiency of lamps. The exact method (a) is free of any assumptions for the value of the maximum luminous efficacy, (b) uses a non-unity spectral exergy-to-energy ratio, and (c) allows choices for the spectral luminous weighting function, which converts broad-spectrum electromagnetic radiation to light. The exact method exposes shortcomings inherent to the conventional method and leads to a reasonable approximation of lamp exergetic efficiency, when needed. To conclude, we provide three recommendations for societal exergy practitioners: use (a) the exact method when a lamp’s spectral power distribution is available, (b) the universal luminous weighting function, and (c) the reasonable approximation to the exact method when a lamp’s luminous efficacy is known but its spectral power distribution is not.